1118 DAYTIME SLEEP, SWS SPINDLE ACTIVITY AND ACUTE EMOTION REGULATION IN SOCIAL ANXIETY DISORDER. (28th April 2017) - Bottary, R; Purcell, S; Pace-Schott, E
Abstract: Introduction: Sleep promotes emotional memory consolidation. Yet, sleep's impact on acute emotion regulation remains largely unknown. We explored daytime sleep's impact on affect, anxiety, and sleepiness following an experimental stressor in individuals with Social Anxiety Disorder (SAD; Experiment-1) and healthy controls (HC; Experiment-2). Methods: Twenty-five SAD and 36 HC subjects completed one (HC) or two (SAD) experimental stressor sessions (SAD: social exposure; HC: viewing highly aversive photographs) followed by a 120-minute PSG-recorded nap (Nap-Condition) or wake (Wake-Condition) opportunity. Positive and Negative Affect Schedule (PANAS+/-),  Spielberger State-Trait Anxiety Inventory-State (STAI-S), and Stanford Sleepiness Scale (SSS) were completed pre- and post-session. For SAD, canonical (13.5Hz), fast (15Hz), and slow (11Hz), spindles were detected bilaterally in artifact-free EEG using co-author S.P.'s open source wavelet analysis program (http://zzz.bwh.harvard.edu ). Spindle amplitude, density and duration was calculated for detected spindles. Results: Experiment 1 : Two (Condition: Nap/Wake) x 2 (Session: 1/2) x 2 (Time-Point: Pre-Session/Post-Session) ANOVAs, performed independently for SSS, PANAS+, PANAS-, and STAI-S scores, revealed main effects of Time-Point for SSS, (Post>Pre; F(1, 24)=12.67, p=0.002), PANAS+, (Post<Pre; F(1, 24)=47.03, p=0.0001), PANAS-, (Post<Pre; F(1, 24)=45.28, p=0.0001), and STAI-S, (Post<Pre; F(1, 24)=15.20,  p=0.0007), and Session for PANAS+, (1>2; F(1, 24)=7.17, p=0.013, and PANAS-, F(1, 24)=7.27, p=0.013, Time-Point x Condition interactions for PANAS+, F(1, 24)=9.29, p=0.006, and PANAS-, F(1, 24)=5.42,  p=0.029, and a Session x Condition interaction for PANAS+, F(1, 24)=9.53, p=0.005. Increased post-nap sleepiness correlated with sleep-onset latency (r=0.69, p=0.03) and fast N3 sleep spindle density (r=0.861, p=0.013) and duration (r=0.808, p=0.028), which also correlated with increased post-nap negative affect (r=0.848, p=0.016). Finally, increased post-nap positive affect correlated with slow N3 spindle duration (r=0.756, p=0.049). Experiment 2: Two (Condition: Nap/Wake) x 2 (Time-Point: Pre-Session/Post-Session) ANOVAs, performed independently for PANAS+, PANAS-, and SSS, revealed a main effect of Time-Point for PANAS+, (Post>Pre; F(1, 34)=6.72, p=0.01), PANAS-, (Post<Pre; F(1, 34)=21.97, p<0.001), and SSS, (Post<Pre; F(1, 34)=7.68, p=0.009), suggesting that both napping and wake increased positive affect, decreased negative affect and reduced sleepiness. Conclusion: Napping dampened positive and negative affect and increased sleepiness in SAD but not HC. For SAD, fast and slow N3 spindle activity differentially impacted emotion regulation and sleepiness. These differing patterns suggest a possible emotion-regulatory deficit of sleep in anxiety disorders. Support (If Any): Research was supported by NIH MH103484, DA11744 and MH48832